Peningkatan Kapasitas UMKM Makanan dan Minuman melalui Strategi Konten Digital dan AI di Lombok Tengah - Ari Satriadi (Jurnal Teknologi Informasi untuk Masyarakat, 2026)
Digital transformation among micro, small, and medium enterprises (MSMEs) requires not only technological skills but also a shift in business actors’ perceptions of the importance of digitalization. This community service program aimed to improve the digital literacy of food and beverage MSME actors in Central Lombok Regency through training on digital content strategy, the use of artificial intelligence (AI) to enhance product visual quality, and the introduction of business digitalization through Google Maps and QRIS. The activity was conducted on May 5, 2026, at the Office of Cooperatives and MSMEs of Central Lombok Regency, involving 25 MSME actors. The method used was Participatory Action Research (PAR), with process- and product-based evaluation. The results showed that more than 80% of participants were able to complete all practical training sessions. In addition to improving technical skills, the program also encouraged a change in participants’ perceptions of the relevance of digital platforms for micro-scale businesses. The use of AI in product visual editing further demonstrated the potential of generative technology as an affordable and practical promotional solution for MSMEs. Therefore, structured and participatory digital literacy training can serve as an empowerment strategy to strengthen MSMEs’ readiness for digital transformation